Fungicidal Mechanisms of Cathelicidins LL-37 and CATH-2 Revealed by Live-Cell Imaging - Ordonez, Soledad R. (American Society for Microbiology, 2014)
Antifungal mechanisms of action of two cathelicidins, chicken CATH-2 and human LL-37, were studied and compared with the mode of action of the salivary peptide histatin 5 (Hst5). Candida albicans was used as a model organism for fungal pathogens. Analysis by live-cell imaging showed that the peptides kill C. albicans rapidly. CATH-2 is the most active peptide and kills C. albicans within 5 min. Both cathelicidins induce cell membrane permeabilization and simultaneous vacuolar expansion. Minimal fungicidal concentrations (MFC) are in the same order of magnitude for all three peptides, but the mechanisms of antifungal activity are very different. The activity of cathelicidins is independent of the energy status of the fungal cell, unlike Hst5 activity. Live-cell imaging using fluorescently labeled peptides showed that both CATH-2 and LL-37 quickly localize to the C. albicans cell membrane, while Hst5 was mainly directed to the fungal vacuole. Small amounts of cathelicidins internalize at sub-MFCs, suggesting that intracellular activities of the peptide could contribute to the antifungal activity. Analysis by flow cytometry indicated that CATH-2 significantly decreases C. albicans cell size. Finally, electron microscopy showed that CATH-2 affects the integrity of the cell membrane and nuclear envelope. It is concluded that the general mechanisms of action of both cathelicidins are partially similar (but very different from that of Hst5). CATH-2 has unique features and possesses antifungal potential superior to that of LL-37.